Utilization of Milk Replacer for Lambs and Kids at Preweaning Period - ., Suprijati (Indonesian Bulletin of Animal and Veterinary Sciences, 2014)
Milk replacer is a mixture of various feed ingredients and feed additives. This paper reviews the formulation of milk replacer, its chemical composition and nutrient requirement, methods of giving milk replacer and effect of milk replacer on the preweaning growth of small ruminant. In the formulation, the available local feed ingredients should be used with consideration of its nutrient composition. Milk replacers could be formulated from skim milk 50-64%, vegetable oil 16-17% or animal fat 20-28%, soy protein 50-57%, whey 35%, cereal or its byproduct 10% and 1-2% vitamin and mineral mix. The recommendation of protein and fat contents were 18-22% and 10-20% for kids, 20-24% and 20-30% for lambs, respectively. Raising the lambs and kids includes feeding colostrum at birth until 3-4 days of life, followed by feeding milk replacer until weaning. At three weeks of life, kids were introduced solid feed, as concentrates or forages. Early weaning could be carried out when the kids reached 9-10 kg of live weight and consumed 120 g/d of solid feed or at the age of 6-8 weeks. Milk replacer formulated according to the recommendation of nutrient requirement gave good performance. Key words: Nutrient composition, performance, milk replacer, feeding method, lamb, kid